Pengaruh Pemberian Reward Dan Punishment Terhadap Motivasi Kerja Karyawan Pada Toserba Mayga Sitanggal - Anis Rakhmawati; Azizah Indriyani; Hendri Sucipto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of reward and punishment on employee motivation at the Mayga Sidinding Department Store. This type of data collection uses a quantitative approach in the form of a survey and gives questionnaires directly to respondents. The population used is all employees who work at the Mayga Department Store, and sampling with the saturation technique is 48 people. Data is processed through the application of Statistical Product and Service (SPSS) version 26 with multiple linear regression analysis techniques. The test results state that individually or partially rewards have a significant effect on employee motivation with a p value of 0.012 <0.05 and a tcount of 2.627 > a ttable of 1.679. Punishment independently or partially has a significant effect on employee motivation, by looking at the probability value 0.000 <0.05 and tcount 3.916> ttable 1.679. This means that punishment has more influence on employee motivation. The result of the next test is that reward and punishment simultaneously affect the work motivation of employees at the Mayga Si Date Department Store.